Improved productivity and zinc content for maize grain by different zinc fertilization techniques in calcareous soils. (7th February 2017) - Sarwar, S.; Rafique, E.; Gill, S. Maqsood; Khan, M. Zameer
ABSTRACT: Scientific management of nutrients along with several other crop management practices are required for sustainable production of maize ( Zea mays L.). Zinc (Zn) status of maize grown in Potohar plateau, Pakistan was monitored. A two-year field study was conducted at two sites to assess the yield of maize cultivars, i.e., hybrid (cv. NARC-2704) and local (cv. Agaiti-2002) and Zn requirement of leaves and grain using various Zn application methods. Zinc was applied by three ways, i.e., broadcast and band placement each at 3, 6 and 9 kg Zn ha −1 ; and foliar at 0.5, 1.0 and 1.5 kg Zn ha −1 along with recommended basal fertilization. Cultivars' response varied to Zn rates, application techniques and sites. The maximum increase in grain yield (two-year mean) at NARC site was: broadcast – hybrid, 17% and local, 13%; band placement – hybrid, 18% and local, 16%; and foliar – hybrid, 15% and local, 13%. Corresponding response at Pindi Gheb site was: broadcast – hybrid, 20% and local, 16%; band placement – hybrid, 21% and local, 17%; and foliar – hybrid, 17% and local, 15%. Zn concentration in leaves and grain of both cultivars also increased to varying extent as a result of applied Zn rates and techniques. Fertilizer Zn requirement for near-maximum grain yield (kg ha −1 ) was: broadcast – hybrid, 4.6 and local, 1.9; band placement – hybrid, 1.8 and local, 1.5; and foliar – hybrid, 0.28 and local, 0.26.